Effects of Ablation Regimes on the Formation and Evolution of Femtosecond Laser-Induced Periodic Structures on Titanium - Lin, Song; Shuo, Wang; Haiyan, Tao; Jingquan, Lin (Frontiers in Physics, 2022)
The formation and evolution of laser-induced periodic structures (LIPSS) have attracted much attention due to their broad applications and rich physics. The literature has shown that excessive laser energy accumulation, such as increasing single pulse energy or cumulative pulse number on a sample, leads to a final fuzzy LIPSS period or even disappearance of the period. This paper discovers a new phenomenon by increasing the laser fluence; the periodic structure appears blurred and disappears in the middle laser fluence region. Two contrary evolution tendencies of the period’s disappearance are observed for the first time. This phenomenon can be attributed to femtosecond ablation regimes in different fluence regions. The experimental results and discussion provide a powerful guarantee for the high-quality preparation of structures by controlling the experimental parameters for future practical applications. The findings of this study play a significant role in regulating the LIPSS period and provide ideas for avoiding the hidden danger of the cycle structure disappearing during the creation of the LIPSS structure, which has practical implications for future LIPSS applications.